Semi-active multi-step predictive control of structures using MR dampers. - Xu, Long-He (Earthquake engineering & structural dynamics.)
A semi-active multi-step predictive control (SAMPC) system with magnetorheological (MR) dampers is developed to reduce the seismic responses of structures. This system can predict the next multi-step responses of structure according to the current state and has a function of self-compensation for time delay that occurred in real application. To study the performance of the proposed control algorithm for addressing time delay and reducing the seismic responses, a numerical example of an 11-story structure with MR dampers is presented. Comparison with the uncontrolled structure indicates that both the peak and the norm values of structural responses are all clearly reduced when the predictive length l⩽10 and the delayed time step d⩽20 are selected, and the SAMPC strategy can guarantee the stability of the controlled structure and reduce the effects of time delay on controlled responses to a certain extent. A performance comparison is also made between the SAMPC strategy and the passive-off and passive-on methods; results indicate that this SAMPC system is more effective than the two passive methods in reducing structural responses subjected to earthquakes.